2011
DOI: 10.1098/rsta.2010.0298
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signatures of the Anthropocene in the Clyde estuary, UK: sediment-hosted Pb, 207/206 Pb, total petroleum hydrocarbon, polyaromatic hydrocarbon and polychlorinated biphenyl pollution records

Abstract: The sediment concentrations of total petroleum hydrocarbons (TPHs), polyaromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), Pb and 207/206 Pb isotope ratios were measured in seven cores from the middle Clyde estuary (Scotland, UK) with an aim of tracking the late Anthropocene. Concentrations of TPHs ranged from 34 to 4386 mg kg −1 , total PAHs from 19 to 16 163 mg kg −1 and total PCBs between less than 4.3 to 1217 mg kg −1 . Inventories, distributions and isomeric ratios of the organic pollutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 44 publications
1
71
1
1
Order By: Relevance
“…A UK study reported P 22 PAH concentrations in the range of <1 to 55 mg/kg (n = 366) (Creaser et al, 2007c). Similarly, Glasgow has soils with P 15 PAH concentrations in the range of 1-52 mg/kg (n = 15) (Morillo et al, 2007;Vane et al, 2011). In contrast, lower amounts of PAH have been observed in urban soils from Wales and the Midlands/Birmingham (Butler et al, 1984;Smith et al, 2001;Wild and Jones, 1995).…”
Section: Comparison Of Data With Other Urban Areasmentioning
confidence: 88%
“…A UK study reported P 22 PAH concentrations in the range of <1 to 55 mg/kg (n = 366) (Creaser et al, 2007c). Similarly, Glasgow has soils with P 15 PAH concentrations in the range of 1-52 mg/kg (n = 15) (Morillo et al, 2007;Vane et al, 2011). In contrast, lower amounts of PAH have been observed in urban soils from Wales and the Midlands/Birmingham (Butler et al, 1984;Smith et al, 2001;Wild and Jones, 1995).…”
Section: Comparison Of Data With Other Urban Areasmentioning
confidence: 88%
“…They note that in the past 200 years, humans in the UK alone have excavated and built up more than four times the volume of Ben Nevis, Britain's highest mountain. Vane et al [24] continue this theme, identifying a range of pollutants preserved in the sediments of the River Clyde that provide a stratigraphical record of the rise of Glasgow, one of the world's first industrial cities.…”
Section: Examining the Anthropocenementioning
confidence: 99%
“…Other significant chemical perturbations include: a twofold increase in the amounts of reactive nitrogen at the Earth's surface and in the oceans, mainly as a consequence of the Haber process and the production of nitrogen-based fertilizers; increases in the amounts of particulate reactive iron (from fly ash), lead, soluble mercury and petroleum-based products as either spills or combustion residues; the introduction of a number of (largely novel) compounds associated with pesticides, flame retardants and other industrial products ( [43] and references therein; see also [44]); and radionuclides associated with fall-out from nuclear explosions.…”
Section: Chemostratigraphymentioning
confidence: 99%